Analysis of the fiscal effort in the collection of the IPTU for the municipalities of the state of Ceará using stochastic boundary model - Sobrinho, Antônio Leal (2019)
Based on the understanding of the low exploitation of the Property Tax and Urban Territorial Tax – IPTU, this paper aims to calculate the Fiscal Effort Index for the municipalities of the State of Ceará during the years 2008 to 2016 regarding IPTU collection. Based on an estimate exercise on different tax collection capabilities and through the use of characteristics from each government sphere, this article seeks to relate the effective and potential capabilities in obtaining these revenues by means of a ranking ordering and classifying the municipalities. The analysis was based on an econometric frontier stochastic model, which expresses the maximum quantity of products that can be obtained from a given quantity of input. Municipalities are shown to be mostly inefficient and mechanisms for improving the collection of IPTU need to be improved.